Five‐year hearing results with the shape memory nitinol stapes prosthesis. (18th August 2014) - Lavy, Jeremy; Khalil, Sherif
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate the long‐term (5‐year) results of the shape‐memory nitinol stapes piston in the surgical treatment of otosclerosis. Study Design Retrospective case review in a tertiary referral center. Methods The patients were adults with clinically proven otosclerosis undergoing stapedotomy. Stapedotomy and ossicular chain reconstruction using a shape‐memory nitinol stapes piston were performed. The main outcome measure was masked air and bone conduction audiometry. Results Forty‐eight out of a potential 58 ears had complete audiometric data. The mean preoperative air‐bone gap was 29.2 dB (standard deviation [SD] 9.4). The postoperative gap at 1 year was 4.6 dB (SD 3.1), and P at 5 years was 7.0 dB (SD 6.2). Conclusions These data suggest that the Smart piston provides a stable long‐term hearing result in the surgical treatment of otosclerosis. Level of Evidence 4. Laryngoscope, 124:2591–2593, 2014